The Slipperiness of 'Global Law'. (17th February 2017) - Collins, Richard
Abstract: What is 'global law'? What is specifically global and specifically legal about global law? Is it even coherent to define law by reference to its 'globality'? These are just some of the questions taken up by Neil Walker in his new book, Intimations of Global Law. In this review essay, I engage critically with Walker's response to these and other questions. Whilst I believe that Walker's mapping of different 'species' of global law is useful and informative in revealing a 'state of the art' of globalising legal trends, his effort to draw these various and not necessarily commensurate species together into a coherent meta-theorisation of global law is, I believe, far less convincing. Walker's conceptualisation of global law is self-defined by reference to its openness, its intimated quality and its 'adjectival' categorisation—characteristics that leave the concept of global law somewhat 'slippery' and malleable to the point of its non-utility in actually helping to guide law's direction, resolve normative disputes or remedy apparent accountability deficits and injustices at the global level.